PENGARUH DESAIN KOMUNIKASI VISUAL ESTETIKA DALAM DAYA BELI KONSUMEN DI MEDIA SOSIAL - Gesnida Yunita (JURNAL Dasarrupa: Desain dan Seni Rupa, 2022)
Aesthetics is a matter that studies the quality or value of the beauty of an object, as well as the impulse power and aesthetic experience of the creator and his observations. In general, the aesthetic understanding of visual arts related to visuals is the emanation of beautiful values, that is, each genre has its own value and aesthetics. This study departs from the problem of aesthetic design in the 4.0 era affecting consumer purchasing power on social media, especially women who are considered to have a high level of consumptiveness compared to men. This study uses a qualitative descriptive research method. Data collection was carried out by interviewing millennials in the city of Bandung. The results of this study indicate that people tend to agree and decide to buy a product on social media if the designs displayed by online shops have aesthetic value in the design of the Instagram feed display.